Proactive coping and social-emotional adjustment among students with and without learning disabilities in Kerala, India - Deepthi, D. P.; Jeyavel, Sundaramoorthy; Subhasree, G.; Jojo, Chacko Eapen (Frontiers in Psychology, 2022)
The current study explored and compared the level of proactive coping and social-emotional adjustment of students with and without learning disabilities. Using a multistage random sampling method researcher selected students with and without learning disabilities; each group consists of 150 participants from different schools in Kerala. The instruments employed in this study were the Proactive Coping Inventory and the Adjustment Inventory for School Students-AISS. Correlation, t-test, and regression analysis were used to analyse the data. The students with learning disabilities have been found to have lower levels of proactive coping and social emotional adjustment than those without learning disabilities. Further, a positive correlation between social emotional adjustment and proactive coping was also observed. The regression analysis has revealed that proactive coping of students with and without learning disabilities was significantly predicting their adjustment. These findings thus emphasize the need to enhance proactive coping among students with learning disabilities in turn to mitigate social emotional adjustment issues.